Peranan Pengadilan Dalam Pelaksanaan Putusan Arbitrase - Muhammad Naufal Hakim (Ethics and Law Journal: Business and Notary, 2024)
Business dispute resolution with adjudication process can be resolved by the parties through litigation or dispute resolution before the court. But this model of settlement is not recommended because the parties are very antagouistic (opposing each other) and also takes a long time. So litigation or dispute resolution before the court is pursued solely as a last resort or if settlement through family or peaceful channels does not find a bright spot or a way out (the last resort or ultimatum remedium). Technically, the function of the court or the duty to adjudicate is formulated as "examining and deciding cases". Deciding a case or a dispute is not always the same as "resolving" or "solving" the case or dispute. Because sometimes a judge's decision is likely to deepen wounds or sharpen disputes (the essence of the dispute has never been resolved) and even with the judge's decision contains the potential or new disputes. Based on the foregoing, it is necessary to change the orientation from "deciding cases" to "resolving cases" The role of the court in the implementation of the arbitration award is primarily as the executor or executor of the arbitration award. In order to be executed, the arbitral award must be registered at the Registrar of the District Court, because if it is not registered, the arbitral award cannot be executed. If there is a delay in registration, the arbitration award can still be executed, but it depends on the consideration of the Chairman of the District Court whether to accept or reject the execution of the arbitration award. Keywords: Court, Arbitration, Court Decision Abstrak Penyelesaian sengketa bisnis dengan proses adjudikasi dapat diselesaikan para pihak melalui jalur litigasi atau penyelesaian sengketa di muka pengadilan. Tetapi penyelesaian model ini tidak direkomendasikan karena para pihak sangat antagouistis (saling berlawanan satu sama lain) dan juga memakan waktu yang lama. Jadi litigasi atau penyelesaian sengketa di muka pengadilan ini ditempuh semata-mata hanya sebagai jalan yang terakhir atau apabila penyelesaian lewat jalur kekeluargaan atau perdamaian tidak menemukan titik terang atau julan keluar (the last resort atau ultimatum remedium). Secara teknis, fungsi pengadilan atau tugas mengadili dirumuskan sebagai “memeriksa dan memutus perkara”. Memutus perkara atau suatu sengketa tidak selalu sama dengan “menyelesaikan” atau “solution” atau “solving” perkara atau sengketa tersebut. Karena terkadang putusan hakim ada kemungkian memperdalam luka-laka atau mempertajam persengketaan (hakikatnya sengketa itu tidak pernah terselesaikan) bahkan dengan putusan hakim tersebut mengandung potensi atau sengketa perselisihan baru. Berdasarkan hal tersebut di atas, maka perlu sekali ada perubahan orientasi dari “memutuskan perkara” menjadi “menyelesaikan perkara” Peranan pengadilan dalam pelaksanaan putusan arbitrase yang paling utama adalah sebagai eksekutor atau pelaksana putusan arbitrase tersebut. Untuk dapat dilaksanakan eksekusi, putusan arbitrase wajib didaftarkan di Panitera Pengadilan Negeri, karena apabila tidak didaftarkan putusan arbitrase tidak dapat dilakukan eksekusi. Apabila terjadi keterlambatan pendaftaran, putusan arbitrase tetap masih bisa dilaksanakan, namun hal itu tergantung pertimbangan dari Ketua Pengadilan Negeri apakah akan menerima atau menolak eksekusi putusan arbitrase tersebut. Kata Kunci: Pengadilan, Arbiterase, Putusan Pengadilan